PELATIHAN SOFTWARE NVIVO UNTUK MENUNJANG PENELITIAN KUALITATIF BAGI MAHASISWA UNIVERSITAS NEGERI SEMARANG - Arief Yulianto; Angga Pandu Wijaya (LP3M STKIP MUHAMMADIYAH MUARA BUNGO, 2022)
There are two research approaches, quantitative and qualitative. The quantitative approach is primarily designated in social research because it is convenient in data collection; while qualitative research is rarely used, only limited researchers understand its advantages. Qualitative software is not familiar to researchers because there are several reasons behind it; therefore, training in using qualitative research software is needed; one of the well-known software is Nvivo. The Nvivo software training was conducted and aimed at students of Postgraduate Degree Study Program at Universitas Negeri Semarang. The training is conducted online by explaining the basics of a qualitative approach, the validity of data, and data processing using the software. Participants were given steps to interpret the data using Nvivo software. The training results show that students have an interest and ability in using qualitative software that can be used to support research activities to complete the final project. The success of the training is measured by the feedback obtained after training to strengthen qualitative research using Nvivo software. The measurement results show that students are satisfied and have increased skills following the training objectives